CODESWITCHING IN AN EFL CLASSROOM: TYPES, FUNCTIONS AND STUDENTS' PERCEPTION - Resmita, Tiara Gardenia (2016)
This study investigated the lecturer and students types and functions of codeswitching in an EFL college class also the students' perception toward classroom codeswitching. The study was conducted at a college in Lampung. The participants of this study were one lecturer who taught English at a class of third- semester and the students of the third semester at that College. This study employed a qualitative research design, embracing the characteristics of a case study. The data were collected through video recording, observation, and questionnaire. The observation was done four weeks which in each week the allocation time was 100 minutes, to capture the types and functions of classroom codeswitching. The interactions were recorded and transcribed, and then coded according to the categorization of types and functions by Poplack (1980), Sert (2005) and Eldridge (1996). The data were also obtained from questionnaire to get the students' perception toward classroom codeswitching. The findings indicated that the types of codeswitching were found in three types: intersentential switching, tag switching and intrasentential switching. The functions of lecturer's codeswitching were found three functions: topic switch, affective functions and repetitive functions, then, for the functions of students' codeswitching there were four functions: equivalence, floorholding, reiteration and conflict control. Moreover, for students' perception toward classroom codeswitching the result was, the students responded positively. It was revealed from the result of the questionnaire which showed that the students felt enthusiasm toward classroom codeswitching or in the other hand the students agreed if teaching and learning process in two languages.;--- Penelitian berjudul Code Switching in an EFL Classroom: types, functions and student's perception adalah Sebuah Studi Kasus Kualitatif di Sebuah Sekolah Tinggi di Lampung berfokus kepada penggunaan alih kode di kelas EFL. Tujuan peneliatian ini adalah untuk (1) menginvestigasi jenis alih kode yang dipergunakan dosen dan mahasiswa dalam kelas EFL, (2) fungsi alih kode yang digunakan dosen dan mahasiswa dikelas, dan (3) mendeskripsikan persepsi mahasiswa terhadap penggunaan alih kode oleh dosen di kelas EFL. Penelitian ini menggunakan metode kualitatif dan data diperoleh melalui observasi kelas, rekaman video, dan kuesioner. Data kemudian dibandingkan dengan teori-teori alih kode, terutama teori Poplack (1980). Subjek penelitian ini adalah seorang dosen Bahasa Inggris laki-laki dan 25 orang mahasiswa semester tiga di Sekolah Tinggi tersebut. Dari penelitian ini ditemukan bahwa (1) jenis alih kode yang digunakan oleh guru di kelas EFL adalah tag-switching, inter-sentential switching, dan intra-sentential switching; (2) fungsinya adalah topic switch, affective functions and repetitive functions, equivalence, floorholding, reiteration and conflict control. (3) persepsi mahasiswa terhadap penggunaan alih kode oleh dosen di kelas EFL secara umum positif, dengan catatan bahwa penggunaan bahasa ibu tidak terlalu berlebihan